Portable Hydro Generator - Othman, Khairulnizam (Multidisciplinary Applied Research and Innovation, 2023)
The final year project that has been selected is a turbine has been named "Portable Hydro Generator". The title was chosen through observation, there is a remote farm in the interior of the village that is often disturbed by animals. Therefore, we conspired to produce a portable hydro generator that generates electricity to the electric fence to prevent animal disturbance. However, the farm is very suitable to carry out our project because it is close to the river water flow which is in line with our goal of creating a portable hydro generator using water flow. As a result of animal disturbance, we came up with an idea to help the farm. Therefore, the main objective of choosing a portable hydro generator as the final year project title is to design and make a portable hydro generator that can be upgraded to run agriculture and be safe from animal disturbance. The manufacture of portable hydro generators is also to channel electricity to LED bulbs so that agriculture can continue at night. Therefore, electricity generation highly recommended nowadays because it is very important and can be used over a long period of time. Next, the scope of this project study is to make installation simulations and evaluate the hydro generator design's effectiveness, including whether it runs smoothly or not. Furthermore, determine the differences in power generation between batteries and hydro generators.